Pemphigus vulgaris: a rare case report - Ramineni, Hari Babu; Yerraguntla, Manasa; Pulimila, Saranya; Kukkapalli, Narendra Babu; Suryadevara, Vidyadhara (International Journal of Research in Medical Sciences, 2017)
Pemphigus Vulgaris (PV) is an organ-specific autoimmune disorder affecting skin and mucous membranes with a characteristic of intraepithelial blistering. The first common sign of this disease is involvement of oral mucosa followed by skin involvement. We here in report a rare case one such recently seen by us, where oral lesions and skin lesions in a 24 year old female patient presenting with a five months history of multiple fluid filled lesions all over the body, who is known case of psychosis finally diagnosed as having pemphigus vulgaris.